Penguatan Masyarakat Dalam Evaluasi Program Sanitasi Sehat Berbasis Penguatan Masyarakat Dalam Evaluasi Program Sanitasi Sehat Berbasis Partisipatif - Rina Anggraini; Supriati; Nur Aini Dewi (STIKES Columbia Asia Medan, 2025)
Assessment and evaluation of sanitation programs that directly involve community participation are crucial for program sustainability. The Community-Based Total Sanitation (STBM) program in Indonesia aims to foster independent hygienic behavior. Participatory approaches such as PHAST (WHO, 1998) emphasize continuous community-led monitoring and self-evaluation as a feedback mechanism. Literature studies show that empowering citizens to evaluate healthy sanitation programs enhances both knowledge and program ownership. For instance, community engagement at SD Kalidadap (Yogyakarta) reported increased participation in waste management and sanitation facility development, as well as improved sanitation awareness and behavior after outreach activities. However, challenges such as limited funding and health resources often hinder optimal participation. This article discusses a participatory evaluation framework and community strengthening strategies, including the establishment of local indicators and the role of facilitators, to support self-assessment in sanitation initiatives. Recommendations include community training, provision of simple evaluation tools, and cross-sector collaboration to improve accountability and sustainability of sanitation programs at the community level.